THE PERFORMANCE OF THREE COMMUNITY HEALTH CENTERS IN DKI JAKARTA BASED UPON BALANCED SCORECARD PERSPECTIVES - Amy Y.S Rahayu; Basita Ginting (Jurnal Penyuluhan, 2006)
Good public health service was an indicator of people’s welfare. In DKI-Jakarta, there was a gap between the expected and the current status of public health. This study investigated the Community Health Center’s performance in delivering health services to the public in DKI-Jakarta. To do so, researcher used the perspective of Balanced Scorecard that included customer satisfaction, financial success, Internal Business Processes, and Learning and Growth aspects. Three community health centers, i.e., one in high income, one in middle income, and one in low income sub-districts were observed in the study. From each health center, fifty customers and ten employees were selected randomly and interviewed in four successive quarters. Of the ten employees interviewed, seven were medical staff and three were non-medical staff. The findings pointed out that the community health centre operated in the high income sub-district performed better than the other two community health centers operated in the middle and in the low income sub-districts. However, further balanced scorecard analysis indicated that the performance of the three community health centers observed in the study should still be improved.